Incidence and risk factors of lower extremity amputations in people with type 2 diabetes in Taiwan, 2001–2010 2001–2010年台湾糖尿病患者的下肢截肢发生率及其相关危险因素的研究. (7th August 2014) - Lai, Yun‐Ju; Hu, Hsiao‐Yun; Lin, Ching‐Heng; Lee, Shih‐Tan; Kuo, Shih‐Chieh; Chou, Pesus
Abstract Background Diabetic patients have an increased risk of lower extremity amputations (LEAs). In the present study we analyzed the incidence of LEA in patients with type 2 diabetes mellitus (T2DM) in Taiwan from 2001 to 2010, and determined risk factors for LEA. Methods Data from the Taiwan National Health Insurance Research Database collected between 1 January 2001 and 31 December 2010 were analyzed. First, the incidence of LEA in the diabetic population was calculated. Subsequently, patients with new‐onset T2DM during the study period were selected, and Cox's proportional hazards model was used to identify factors associated with LEA. The characteristics of patients who underwent major and multiple amputations were also analyzed. Results From 2001 to 2010, 1588 non‐traumatic LEAs were performed among the study subjects; 776 (48.9%) were minor and 812 (51.1%) were major LEAs. Over the period in question, the incidence of LEAs decreased from 3.08 to 1.65 per 1000 person‐years. Factors associated with LEA included peripheral arterial occlusive disease (hazard ratio [HR] 4.134; 95% confidence interval [CI] 2.72–6.29), diabetic neuropathy (HR 2.34; 95% CI 1.62–3.38), diabetic retinopathy (HR 2.07; 95% CI 1.12–3.82), heart failure (HR 2.13; 95% CI 1.45–3.15), male gender (HR 1.64; 95% CI 1.24–2.18), and adult onset diabetes (HR 1.02; 95% CI 1.01–1.04). Patients with a history of stroke were more likely to undergo major and multiple amputations (P < 0.001 and P < 0.01, respectively). Conclusions The incidence of LEA in the Taiwan diabetic population decreased over the study period. The results indicate that efforts to improve diabetic care should be supported and sustainable, especially for those at high risk.